Air electrode catalyst for air secondary battery, method for producing same, and air secondary battery

By synthesizing bismuth ruthenium composite oxide with a pyrochroa-type crystal structure and specific EXAFS vibration peak intensity ratios, the issue of internal short circuits in air secondary batteries is addressed, resulting in enhanced cycle life characteristics.

JP7648401B2Active Publication Date: 2025-03-18FDK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021021020
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-12
Publication Date
2025-03-18
Estimated Expiration
2041-02-12

AI Technical Summary

Technical Problem

Air secondary batteries using pyrochrole-type bismuth ruthenium composite oxide as the air electrode catalyst suffer from internal short circuits, leading to premature battery life exhaustion.

Method used

A bismuth ruthenium composite oxide with a pyrochroa-type crystal structure, represented by Bi2Ru2O7, is synthesized with a specific strength ratio of peak intensities in the EXAFS vibration spectra, ranging from 0.28 to 0.44, to enhance structural stability and suppress bismuth elution.

Benefits of technology

The improved structural stability of the bismuth ruthenium composite oxide effectively suppresses bismuth dendrite growth and internal short circuits, thereby extending the cycle life of air secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648401000002
    Figure 0007648401000002
  • Figure 0007648401000003
    Figure 0007648401000003
  • Figure 0007648401000004
    Figure 0007648401000004
Patent Text Reader

Abstract

To provide an air electrode catalyst for an air secondary battery, which can suppress the occurrence of internal short circuit in comparison to conventional one, and therefore enables the enhancement of the cycle life characteristic, and a manufacturing method thereof, and an air secondary battery.SOLUTION: A battery 2 comprises: an electrode group 10 including an air electrode 16 and a negative electrode 12 which are put on each other through a separator 14; and a container 4 in which the electrode group 10 is encased together with an alkaline electrolyte solution. The air electrode 16 contains a bismuth ruthenium composite oxide having a pyrochlore-type crystalline structure of which the compositional formula is represented by Bi2Ru2O7. With the bismuth ruthenium composite oxide, when "A" is an intensity of a peak located in a range of 3.2Å-1<k<4.9Å-1 in k3χ(k) vibration spectra gained according to EXAFS measurement of Bi-L3, and "B" is an intensity of a peak located in a range of 4.9Å-1<k<5.7Å-1, B / A, i.e. the intensity ratio of A and B is given as follows: 0.28<B / A<0.44.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an air electrode catalyst for an air secondary battery, a method for producing the same, and an air secondary battery. [Background technology]

[0002] In recent years, air batteries, which use oxygen in the air as the positive electrode active material, have been attracting attention because of their high energy density, small size, and ease of weight reduction, etc. Among such air batteries, zinc-air primary batteries have been put to practical use as power sources for hearing aids.

[0003] Additionally, research is being conducted on rechargeable air batteries that use Li, Zn, Al, Mg, etc. as the negative electrode metal, and such air secondary batteries are expected to become new secondary batteries that may have the potential to exceed the energy density of lithium-ion secondary batteries.

[0004] As one type of such air secondary battery, an air-hydrogen secondary battery is known, which uses an alkaline aqueous solution (alkaline electrolyte) as the electrolyte and hydrogen as the negative electrode active material (see, for example, Patent Document 1). Air-hydrogen secondary batteries as typified by Patent Document 1 use a hydrogen storage alloy as the negative electrode metal, but the negative electrode active material in air-hydrogen secondary batteries is hydrogen that is absorbed and released by the above-mentioned hydrogen storage alloy, so that no dissolution or deposition reaction of the hydrogen storage alloy itself occurs during chemical reactions (hereinafter also referred to as battery reactions) during charging and discharging in the battery. For this reason, air-hydrogen secondary batteries have the advantage that they do not cause problems such as internal short circuit caused by so-called dendrite growth, in which the negative electrode metal precipitates in a dendritic form, or a decrease in battery capacity caused by shape change.

[0005] In an air secondary battery that uses an alkaline electrolyte, such as the above-mentioned air hydrogen secondary battery, the following charge and discharge reactions occur in the positive electrode (hereinafter also referred to as the air electrode).

[0006] Charging (oxygen generation reaction): 4OH - →O2+2H2O+4e- (I) Discharge (oxygen reduction reaction): O2 + 2H2O + 4e - →4OH - (II)

[0007] As shown in reaction formula (I), oxygen is generated at the air electrode during charging in an air secondary battery. This oxygen passes through the voids inside the air electrode and is released into the atmosphere from the part of the air electrode that is open to the atmosphere. On the other hand, during discharging, oxygen taken in from the atmosphere is reduced to generate hydroxide ions as shown in reaction formula (II).

[0008] A catalyst that promotes the above-mentioned charge and discharge reaction is used for the air electrode, which is the positive electrode of the above-mentioned air secondary battery. In air secondary batteries, it is desired to reduce the overvoltage in the charge and discharge reaction of the air electrode in order to improve energy efficiency and increase output. For this reason, materials that are effective in reducing the overvoltage have been studied as materials that serve as catalysts for use in the air electrode. As such materials that are effective in reducing the overvoltage, various metal oxides are promising. Among such metal oxides, pyrochlore-type bismuth ruthenium composite oxides have the above-mentioned "dual function" of oxygen generation and oxygen reduction, and can reduce the overvoltage in both the charge reaction and the discharge reaction, making them particularly promising as air electrode catalysts.

[0009] By the way, when an air secondary battery using a pyrochlore-type bismuth ruthenium composite oxide as an air electrode is repeatedly used, an internal short circuit may occur, and the battery may run out of life early. This internal short circuit is caused by the dissolution and precipitation reaction of bismuth. In detail, bismuth dissolves from the air electrode, bismuth ions are generated, and these bismuth ions diffuse in the electrolyte to reach the negative electrode, where they are reduced to metallic bismuth and precipitate. Then, this metallic bismuth grows into a dendrite and grows in a dendritic shape. The bismuth dendrites grow into the separator and eventually penetrate the separator. As a result, an internal short circuit occurs. When such an internal short circuit occurs, not only ionic conductivity through the electrolyte but also electronic conductivity exists between the positive and negative electrodes inside the battery. When electronic conductivity exists, the battery is self-discharging. As a result, the discharge capacity of the battery decreases with a relatively small number of cycles, and the cycle life becomes shorter.

[0010] Since the pyrochlore-type bismuth ruthenium composite oxide is a catalyst, it is considered that dissolution and precipitation of bismuth from the bismuth ruthenium composite oxide itself does not usually occur with the charge and discharge reaction of the air secondary battery. However, in reality, the above-mentioned internal short circuit occurs, and various studies on the problem of this internal short circuit have been conducted. In such a study, Patent Document 2 found that by-products containing bismuth generated in the process of producing the pyrochlore-type bismuth ruthenium composite oxide may be the cause of the internal short circuit. Patent Document 2 also discloses a method for producing a catalyst for an air secondary battery that can remove the by-products. In detail, Patent Document 2 discloses a method for producing a pyrochlore-type bismuth ruthenium composite oxide, which includes a coprecipitation step of synthesizing a precursor by a coprecipitation method, a calcination step of calcining the precursor, and an acid treatment step of removing the by-products from the calcined product obtained in the calcination step by acid treatment. According to Patent Document 2, if the acid treatment step is not carried out, bismuth will dissolve and precipitate from the by-products, causing an internal short circuit. However, it is described that by carrying out this acid treatment step, internal short circuits can be suppressed, and the cycle life of the battery can be extended. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2016-152068 A [Patent Document 2] JP 2019-179592 A Summary of the Invention [Problem to be solved by the invention]

[0012] However, in order to put air secondary batteries into practical use, there is a demand for a longer life. However, in air secondary batteries using a pyrochlore-type bismuth ruthenium composite oxide obtained by adopting the method for producing a catalyst for air secondary batteries described in Patent Document 2 as a catalyst in the air electrode, the current situation is that a cycle life long enough to withstand practical use has not been obtained. In other words, it is believed that the suppression of internal short circuits is still insufficient.

[0013] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide an air electrode catalyst for an air secondary battery that can suppress the occurrence of internal short circuits more effectively than before, thereby improving cycle life characteristics, a method for producing the same, and an air secondary battery. [Means for solving the problem]

[0014] In order to achieve the above object, the present invention provides a bismuth ruthenium composite oxide having a pyrochlore-type crystal structure represented by the composition formula Bi2Ru2O7, and a k 3 3.2 Å in the vibrational spectrum of χ(k) -1 <k<4.9Å -1 The intensity of the peak in the range of 4.9 Å is defined as A. -1 <k<5.7Å -1 When the intensity of the peak existing in the range is B, the intensity ratio B / A of A and B is 0.28 Effect of the Invention

[0015] The air electrode catalyst for an air secondary battery according to the present invention is a bismuth ruthenium composite oxide having a pyrochlore-type crystal structure represented by the composition formula Bi2Ru2O7, and has a k 3 3.2 Å in the vibrational spectrum of χ(k) -1 <k<4.9Å -1 ​The intensity of the peak in the range of 4.9 Å is defined as A. -1 <k<5.7Å -1 When the intensity of the peak existing in the range is B, the intensity ratio B / A of A and B is 0.28 [Brief description of the drawings]

[0016] [Figure 1] 1 is a cross-sectional view illustrating an air hydrogen secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a perspective view showing a crystal structure model of the pyrochlore structure of Bi2Ru2O7. [Diagram 3] 1 is a graph showing the absorption spectrum of the Bi2Ru2O7 catalyst of Example 1. [Figure 4] 1 is a graph showing a normalized absorption spectrum of the Bi2Ru2O7 catalyst of Example 1. [Diagram 5] 1 is a graph showing the EXAFS vibration spectrum of the Bi2Ru2O7 catalyst of Example 1. [Figure 6] This is a graph obtained by performing a Fourier transform (FT) on FIG. 5. [Figure 7] 1 is a graph showing the absorption spectrum of the Bi2Ru2O7 catalyst of Comparative Example 1. [Figure 8] 1 is a graph showing a normalized absorption spectrum of the Bi2Ru2O7 catalyst of Comparative Example 1.​ [Figure 9] 1 is a graph showing the EXAFS vibration spectrum of the Bi2Ru2O7 catalyst of Comparative Example 1. [Figure 10] This is a graph obtained by performing a Fourier transform (FT) on FIG. [Figure 11] 1 is a graph showing the relationship between the peak intensity ratio B / A of EXAFS oscillations and the number of cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an air hydrogen secondary cell 2 (hereinafter referred to as cell 2) including an air electrode catalyst for an air secondary cell according to this embodiment will be described with reference to the drawings.

[0018] As shown in FIG. 1, the battery 2 includes a container 4 and an electrode group 10 placed in the container 4 together with an alkaline electrolyte 82 .

[0019] The electrode group 10 is formed by stacking a negative electrode 12 and an air electrode (positive electrode) 16 with a separator 14 interposed therebetween.

[0020] The negative electrode 12 includes a conductive negative electrode substrate having a porous structure and a large number of pores, and a negative electrode mixture supported in the pores and on the surface of the negative electrode substrate. For example, foamed nickel can be used as the negative electrode substrate.

[0021] The negative electrode mixture includes a hydrogen storage alloy powder as a negative electrode active material, which is an aggregate of hydrogen storage alloy particles capable of absorbing and releasing hydrogen, a conductive material, and a binder. The conductive material may be a powder that is an aggregate of particles such as graphite or carbon black.

[0022] The hydrogen storage alloy constituting the hydrogen storage alloy particles is not particularly limited, but for example, a rare earth-Mg-Ni based hydrogen storage alloy is preferably used. The composition of this rare earth-Mg-Ni based hydrogen storage alloy can be freely selected, but for example, General formula: Ln 1-a Mg aNi b-c-d Al c M d (III) It is preferable to use one represented by the following formula:

[0023] In general formula (III), Ln represents at least one element selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, Y, Zr, and Ti; M represents at least one element selected from the group consisting of V, Nb, Ta, Cr, Mo, Mn, Fe, Co, Ga, Zn, Sn, In, Cu, Si, P, and B; and the subscripts a, b, c, and d represent numbers satisfying the relationships 0.01≦a≦0.30, 2.8≦b≦3.9, 0.05≦c≦0.30, and 0≦d≦0.50, respectively.

[0024] The hydrogen storage alloy particles can be obtained, for example, as follows. First, metal raw materials are weighed and mixed to obtain a desired composition, and the mixture is melted in an inert gas atmosphere, for example, in a high-frequency induction melting furnace, and then cooled to form an ingot. The resulting ingot is heated to 900 to 1200°C in an inert gas atmosphere, and is homogenized by heat treatment in which it is held at that temperature for 5 to 24 hours. The ingot is then crushed and sieved to obtain a hydrogen storage alloy powder, which is an aggregate of hydrogen storage alloy particles of a desired particle size.

[0025] As the binder, for example, sodium polyacrylate, carboxymethyl cellulose, styrene butadiene rubber, etc. are used.

[0026] Here, the negative electrode 12 can be produced, for example, as follows. First, a negative electrode mixture paste is prepared by kneading hydrogen storage alloy powder, which is an aggregate of hydrogen storage alloy particles, a conductive material, a binder, and water. The obtained negative electrode mixture paste is filled into a negative electrode substrate, which is then dried. After drying, the negative electrode substrate to which the hydrogen storage alloy particles and the like are attached is rolled to increase the amount of alloy per unit volume, and then cut to obtain a negative electrode 12. This negative electrode 12 has a plate shape as a whole. The negative electrode mixture layer included in the negative electrode 12 is formed of hydrogen storage alloy particles, conductive material particles, and the like, and therefore has a porous structure.

[0027] Next, the air electrode 16 includes a conductive air electrode substrate having a porous structure and a large number of pores, and an air electrode mixture layer (positive electrode mixture layer) supported in the pores and on the surface of the air electrode substrate. For example, nickel foam or nickel mesh can be used as the air electrode substrate.

[0028] The air electrode mixture contains an air electrode catalyst for an air secondary battery, a conductive material, and a binder. Bismuth ruthenium composite oxide is used as the air electrode catalyst for air secondary batteries. Bismuth ruthenium composite oxide has the dual functions of oxygen generation and oxygen reduction, and such a dual-function catalyst contributes to reducing the overvoltage of the battery both during the charging and discharging processes.

[0029] The bismuth ruthenium composite oxide of this embodiment has a pyrochlore-type crystal structure represented by the composition formula Bi2Ru2O7, and has a k 3 3.2 Å in the vibrational spectrum of χ(k) -1 <k<4.9Å -1 The intensity of the peak in the range of 4.9 Å is defined as A. -1 <k<5.7Å -1 When the intensity of the peak existing in the range is B, the intensity ratio B / A of A and B is 0.28

[0030] ​In this embodiment, the bismuth ruthenium composite oxide having the pyrochlore-type crystal structure represented by the composition formula BiRuO includes a bismuth ruthenium composite oxide mainly having a crystal structure similar to the pyrochlore-type crystal structure represented by the composition formula BiRuO.

[0031] In addition, the bismuth ruthenium composite oxide of the present embodiment preferably contains at least one element selected from Na, Ca, Pb, rare earth elements, Ir, Mn, Ti, V, Nb, and Mo.

[0032] Furthermore, it is more preferable that the molar ratio Bi / Ru of Bi and Ru contained in the bismuth ruthenium composite oxide of this embodiment is 0.75≦Bi / Ru≦0.80.

[0033] The crystal structure of the Bi2Ru2O7 pyrochlore type is shown in Figure 2. This figure shows a structure in which a Ru-O network composed of RuO6 octahedra and a Bi-O' network are nested inside each other. This pyrochlore type crystal structure corresponds to a defect structure in which 2 x 2 x 2 = 8 fluorite lattices are stacked and one oxygen atom is removed. This fluorite type unit lattice has a large space surrounded by eight oxygen ions inside, allowing the oxygen ions to move relatively easily. Furthermore, the mobility of oxygen ions tends to be further increased by structural distortion and oxygen deficiency of O' atoms, which is thought to have a dominant effect on catalytic reactions involving the movement of lattice oxygen.

[0034] In order to extend the cycle life of an air secondary battery using an air electrode containing a bismuth ruthenium composite oxide having such a pyrochlore crystal structure as a catalyst, the present inventors have conducted extensive research. In the process, they found that there is a significant amount of dissolution of bismuth from the bismuth ruthenium composite oxide itself, and that the dissolution of bismuth is one of the causes of internal short circuits. Therefore, they focused on the crystal structure of the bismuth ruthenium composite oxide described above and investigated whether it is possible to improve the dissolution resistance from the crystal structure level.

[0035] X-ray diffraction (XRD) is generally used to investigate crystal structures. However, to observe the local structure (interatomic distance, coordination number, structural disorder, etc.) of a target element more microscopically, extended X-ray absorption fine structure (EXAFS) measurements are superior. EXAFS measurements measure the X-ray absorption spectrum of a sample and investigate the vibration spectrum near the absorption edge corresponding to the ionization of inner shell electrons. The photoelectron wave emitted with X-ray absorption interferes with the scattered wave returned from nearby atoms, changing the transition probability of X-ray absorption. The vibration component generated contains information on the local structure around the target element. Therefore, the vibration spectrum of EXAFS can observe local structural information limited to Bi element.

[0036] The present inventors improved the synthesis conditions of the catalyst (bismuth ruthenium composite oxide), performed EXAFS measurements on the obtained bismuth ruthenium composite oxide, and investigated the relationship between the EXAFS vibration of the Bi element and the internal short circuit. -1 <k<4.9Å -1 The intensity A of the peak in the range of 4.9 Å -1 <k<5.7Å -1 The ratio B / A of the intensity of the peaks in the range of

[0037] ​According to EXAFS, it is also possible to extract a radial structure distribution that reflects the atomic distribution in one-dimensional direction with respect to Bi by Fourier transforming the EXAFS vibration. Peaks are observed in the order of distorted dodecahedral O atoms around Bi, adjacent Bi and Ru atoms, and O atoms from the nearest side. It is presumed that the bismuth ruthenium composite oxide of this embodiment has a larger distortion of the nearest O atom coordination than the conventional bismuth ruthenium composite oxide, and has a clear amplitude of the peak even at a long distance, resulting in high crystallinity. These are thought to contribute to the dissolution resistance. However, the details have not been elucidated because accurate radial distribution analysis requires suppressing atomic vibration in an extremely low temperature environment, performing a measurement with a high S / N ratio up to the higher energy side, and widening the Fourier transform range.

[0038] Furthermore, in order to improve the dissolution resistance and activity of bismuth ruthenium oxide, it is believed to be effective to replace some of the Bi and Ru with different atoms. For example, the Bi site has an ionic radius close to that of Na, Ca, Pb, and rare earth elements (Nd, Sm), and there are reports of it forming a pyrochlore structure with Ru and similar elements. These elements, including Bi, do not themselves have redox activity, and are thought to contribute to the stabilization of the structure. By replacing some of the Bi with these atoms, it is expected that the dissolution resistance and cycle characteristics will be further improved. In addition, although these elements themselves do not have redox activity, Bi 3+ By replacing it with an atom of a different valence, the valence of Ru changes, and it is expected that the catalytic activity will improve. Ru has a similar ionic radius to Ir, Mn, Ti, V, Nb, and Mo, which are also transition metals, and is known to have a pyrochlore structure. By replacing a part of Ru with these atoms, there is a possibility that the catalytic activity will improve due to a synergistic effect in the reaction elementary process and an increase in the mobility of O atoms due to structural distortion. The dissolution of Bi from these substitutional bismuth ruthenium oxides is also determined by the valence and local structure of Bi, so the relationship between the EXAFS vibration of the Bi element and internal short circuit is similar.

[0039] Next, the method for producing the bismuth ruthenium composite oxide according to this embodiment will be specifically described below.

[0040] First, prepare Bi(NO3)3·5H2O and RuCl3·3H2O. Then, measure out Bi(NO3)3·5H2O and RuCl3·3H2O so that the molar ratio of Ru is 1.00 and Bi is 0.75 to 0.80. The measured Bi(NO3)3·5H2O and RuCl3·3H2O are put into a specified solution and stirred to prepare a mixed aqueous solution of Bi(NO3)3·5H2O and RuCl3·3H2O. At this time, the specified solution can be distilled water or a dilute nitric acid solution, and the temperature of these solutions is 60°C to 90°C. Then, add a 1 mol / L to 3 mol / L NaOH aqueous solution to this mixed aqueous solution to precipitate a sparingly soluble salt (precursor) (coprecipitation process). In this case, if the pH in the mixed aqueous solution becomes non-uniform, the particles obtained may become polydispersed or the composition distribution may become non-uniform, so it is preferable to vigorously stir the solution to make the pH of the entire solution uniform. Due to the pH dependency of the solubility of poorly soluble salts, the pH during coprecipitation is preferably 10 or more. Furthermore, the pH is most preferably 11 or more. This is because when the pH is low and the solubility is high, Ostwald ripening progresses and coarse particles are easily formed. After that, while bubbling oxygen gas, an aging treatment is performed for 12 to 48 hours, and the precipitate is collected by suction filtration. After that, the collected precipitate is dried to evaporate a part of the water (drying process). This results in a dried precipitate. In this case, in order to suppress the coarsening of particles and the decrease in specific surface area due to sintering in the subsequent firing process, it is desirable to remove as much water as possible in the drying process, and the drying temperature is preferably 80°C or more and 200°C or less, and the drying time is preferably 1 hour or more.

[0041] The dried precipitate obtained as described above is placed in a mortar and crushed with a pestle to obtain a precursor powder. The precursor powder obtained is then heated to a temperature of 300°C or higher and 700°C or lower in an air atmosphere and held for 0.5 hours or higher and 24 hours or lower to perform a heat treatment (sintering process). This heat treatment can improve the crystallinity. Here, a more preferable firing temperature is 400°C or higher and 600°C or lower. This is because if the firing temperature is too low, pyrochlore type crystals with low crystallinity are obtained, and if the firing temperature is too high, sintering causes particle coarsening and a decrease in the specific surface area.

[0042] After the heat treatment (calcination treatment), the precursor is washed with distilled water at 60°C or higher and 90°C or lower, and then heated to 100°C or higher and 130°C or lower for drying. As a result, the composition formula becomes Bi2Ru2O 7-z (where z satisfies the relationship 0≦z≦1), a bismuth ruthenium composite oxide having a pyrochlore type crystal structure represented by the formula:

[0043] Next, it is preferable to immerse the obtained bismuth ruthenium composite oxide in an aqueous solution of nitric acid to perform an acid treatment. Specifically, the procedure is as follows.

[0044] First, prepare an aqueous solution of nitric acid. The concentration of the aqueous solution of nitric acid is preferably 5 mol / L or less. The amount of the aqueous solution of nitric acid is preferably 20 mL per 1 g of bismuth ruthenium composite oxide. The temperature of the aqueous solution of nitric acid is preferably set to 20°C or more and 25°C or less.

[0045] Then, the bismuth ruthenium composite oxide is immersed in the prepared nitric acid aqueous solution and stirred for 6 hours or less. After a predetermined time has passed, the bismuth ruthenium composite oxide is suction filtered from the nitric acid aqueous solution. The filtered bismuth ruthenium composite oxide is put into distilled water set at 60°C or higher and 80°C or lower and washed.

[0046] The washed bismuth ruthenium composite oxide is subjected to a drying treatment in which it is maintained in an environment of 100° C. or higher and 130° C. or lower for 1 hour or longer and 4 hours or shorter.

[0047] In this manner, an acid-treated bismuth ruthenium composite oxide is obtained. By carrying out the acid treatment in this manner, by-products generated during the manufacturing process of the bismuth ruthenium composite oxide can be removed. The acidic aqueous solution used in the acid treatment is not limited to an aqueous nitric acid solution, and in addition to the aqueous nitric acid solution, an aqueous hydrochloric acid solution or an aqueous sulfuric acid solution can be used. The aqueous hydrochloric acid solution and the aqueous sulfuric acid solution also have the effect of removing by-products, similar to the aqueous nitric acid solution.

[0048] The bismuth ruthenium composite oxide obtained as described above is mechanically pulverized as necessary to adjust the particle size to a predetermined size, thereby obtaining a powder of the bismuth ruthenium composite oxide which is an aggregate of particles having the predetermined particle size.

[0049] Next, the conductive material will be described. This conductive material is used to reduce the internal resistance in order to increase the output of the air secondary battery, and as a carrier for the above-mentioned catalyst. For example, nickel powder, which is an aggregate of nickel particles, is preferably used as such a conductive material. For example, particles having an average particle size of 0.1 μm to 10 μm are preferably used as the above-mentioned nickel particles. Here, in this embodiment, when referring to the average particle size, unless otherwise specified, it refers to the volume average particle size obtained by measuring the particle size distribution on a volume basis for the powder, which is an aggregate of the target particles, using a laser diffraction / scattering type particle size distribution measuring device.

[0050] The nickel powder is preferably contained in the air electrode mixture in an amount of 60% by weight or more. The upper limit of the content of the nickel powder is preferably 80% by weight or less in relation to other constituent materials in the air electrode mixture. In addition, it is preferable to use filament-shaped nickel powder as the nickel powder.

[0051] The binder binds the constituent materials of the air electrode mixture and also serves to impart appropriate water repellency to the air electrode 16. The binder is not particularly limited, and may be, for example, a fluororesin. A preferred example of the fluororesin is polytetrafluoroethylene (PTFE).

[0052] The air electrode 16 can be manufactured, for example, as follows. First, a catalyst powder which is an aggregate of bismuth ruthenium composite oxide particles, a conductive powder which is an aggregate of Ni particles as a conductive material, a binder, and water are prepared. Then, the catalyst powder, conductive powder, binder, and water are kneaded to prepare an air electrode mixture paste.

[0053] The obtained air electrode mixture paste is formed into a sheet shape, for example, by applying a roller press, thereby obtaining an air electrode mixture sheet. The air electrode mixture sheet is then press-bonded to a nickel mesh (air electrode substrate), thereby obtaining an intermediate air electrode product.

[0054] Next, the obtained intermediate product is put into a firing furnace and subjected to firing treatment. This firing treatment is performed in an inert gas atmosphere. For example, nitrogen gas or argon gas is used as the inert gas. The firing treatment conditions are heating to a temperature of 300°C or more and 400°C or less, and maintaining this state for 10 minutes or more and 20 minutes or less. After that, the intermediate product is naturally cooled in the firing furnace, and when the temperature of the intermediate product becomes 150°C or less, it is taken out into the air. In this way, an intermediate product subjected to firing treatment is obtained. The intermediate product after the firing treatment is cut into a predetermined shape to obtain an air electrode 16. This air electrode 16 has an air electrode mixture layer formed by an air electrode mixture. Since the air electrode mixture contains particles of bismuth ruthenium composite oxide, the air electrode mixture layer formed by such an air electrode mixture has a porous structure as a whole and has excellent gas diffusion properties.

[0055] The air electrode 16 and the negative electrode 12 obtained as described above are stacked with a separator 14 interposed therebetween, thereby forming an electrode group 10. This separator 14 is disposed to prevent a short circuit between the air electrode 16 and the negative electrode 12, and an electrically insulating material is used for it. Examples of materials that can be used for this separator 14 include a polyamide fiber nonwoven fabric to which a hydrophilic functional group has been imparted, and a polyolefin fiber nonwoven fabric such as polyethylene or polypropylene to which a hydrophilic functional group has been imparted.

[0056] The formed electrode group 10 is placed in a container 4 together with an alkaline electrolyte. The container 4 is not particularly limited as long as it can accommodate the electrode group 10 and the alkaline electrolyte, and for example, an acrylic box-shaped container 4 is used. For example, as shown in FIG. 1, the container 4 includes a container body 6 and a lid 8.

[0057] The container body 6 is shaped like a box and has a bottom wall 18 and a side wall 20 extending upward from the peripheral portion of the bottom wall 18. The portion surrounded by the upper edge 21 of the side wall 20 is open. In other words, an opening 22 is provided on the opposite side of the bottom wall 18. Furthermore, in the side wall 20, through holes are provided at predetermined positions in each of the right side wall 20R and the left side wall 20L, and these through holes become outlets 24, 26 for lead wires, which will be described later.

[0058] Furthermore, an electrolyte storage unit 80 is attached to the container body 6. The electrolyte storage unit 80 is a container that stores an alkaline electrolyte 82, and is attached, for example, via a connection unit 84 that communicates with a through-hole 19 provided in the bottom wall 18. The connection unit 84 is a flow path for the alkaline electrolyte 82 that communicates between the inside of the container 4 and the electrolyte storage unit 80. Since the inside of the container 4 and the electrolyte storage unit 80 are thus communicated with each other, the alkaline electrolyte 82 can move between the inside of the container 4 and the electrolyte storage unit 80.

[0059] The lid 8 has the same shape as the container body 6 in a plan view, and is placed on the upper part of the container body 6 to close the opening 22. The gap between the lid 8 and the upper edge 21 of the side wall 20 is liquid-tightly sealed.

[0060] The lid 8 has an air passage 30 on the inner surface 28 facing the inside of the container body 6. The air passage 30 is open at the portion facing the inside of the container body 6, and has a serpentine shape as a whole. Furthermore, the lid 8 has an inlet air hole 32 and an outlet air hole 34 penetrating in the thickness direction at a predetermined position. The inlet air hole 32 communicates with one end of the air passage 30, and the outlet air hole 34 communicates with the other end of the air passage 30. That is, the air passage 30 is open to the atmosphere through the inlet air hole 32 and the outlet air hole 34. It is preferable to attach a pressure pump (not shown) to the inlet air hole 32. By driving this pressure pump, air can be sent from the inlet air hole 32 to the air passage 30.

[0061] If necessary, an adjustment member 36 is placed on the bottom wall 18 of the container body 6. The adjustment member 36 is used to align the electrode group 10 in the height direction inside the container 4. As the adjustment member 36, for example, a foamed nickel sheet is used.

[0062] The electrode group 10 is disposed on the adjustment member 36. At this time, the negative electrode 12 of the electrode group 10 is disposed so as to be in contact with the adjustment member 36.

[0063] On the other hand, a water-repellent ventilation member 40 is disposed on the air electrode 16 side of the electrode group 10 so as to contact the air electrode 16. This water-repellent ventilation member 40 is a combination of a PTFE porous membrane 42 and a nonwoven diffusion paper 44. The water-repellent ventilation member 40 exhibits a water-repellent effect due to the PTFE and allows gas to pass through. The water-repellent ventilation member 40 is interposed between the lid 8 and the air electrode 16 and is in close contact with both the lid 8 and the air electrode 16. This water-repellent ventilation member 40 has a size sufficient to cover the entire ventilation path 30, the inlet ventilation hole 32, and the outlet ventilation hole 34 of the lid 8.

[0064] The container body 6 housing the electrode group 10, the adjusting member 36, and the water-repellent and breathable member 40 as described above is covered with the lid 8. Then, as illustrated diagrammatically in Fig. 1, peripheral edge portions 46, 48 of the container 4 (container body 6 and lid 8) are sandwiched from above and below by connectors 50, 52. Thereafter, a predetermined amount of alkaline electrolyte 82 is injected from the electrolyte reservoir 80, and the container 4 is filled with the alkaline electrolyte 82. In this manner, the battery 2 is formed.

[0065] As the alkaline electrolyte 82, a typical alkaline electrolyte used in alkaline secondary batteries is suitably used, and specifically, an aqueous solution containing at least one of NaOH, KOH, and LiOH as a solute is used.

[0066] Here, in the battery 2, the ventilation passage 30 of the lid 8 faces the water-repellent ventilation member 40. The water-repellent ventilation member 40 allows gas to pass but blocks moisture, so the air electrode 16 is open to the atmosphere via the water-repellent ventilation member 40, the ventilation passage 30, the inlet ventilation hole 32, and the outlet ventilation hole 34. In other words, the air electrode 16 comes into contact with the atmosphere through the water-repellent ventilation member 40.

[0067] In the battery 2, an air electrode lead (positive electrode lead) 54 is electrically connected to the air electrode (positive electrode) 16, and a negative electrode lead 56 is electrically connected to the negative electrode 12. The air electrode lead 54 and the negative electrode lead 56 are drawn generally in FIG. 1, but are drawn out of the container 4 from the outlets 24, 26 while maintaining airtightness and liquid tightness. An air electrode terminal (positive electrode terminal) 58 is provided at the tip of the air electrode lead 54, and a negative electrode terminal 60 is provided at the tip of the negative electrode lead 56. In the battery 2, the air electrode terminal 58 and the negative electrode terminal 60 are used to input and output current during charging and discharging.

[0068] [Example] 1. Battery manufacturing Example 1 (1) Manufacturing of air electrode catalyst 1) Co-precipitation process Bi(NO3)3·5H2O and RuCl3·3H2O were prepared. Bi(NO3)3·5H2O and RuCl3·3H2O were weighed so that the molar concentration ratio of Ru was 1.00 and Bi was 0.75. The weighed Bi(NO3)3·5H2O and RuCl3·3H2O were put into a 2.6 mol / L nitric acid solution at 75°C and stirred to prepare a mixed aqueous solution of Bi(NO3)3·5H2O and RuCl3·3H2O. 2L of the nitric acid solution was prepared. Then, a 2 mol / L NaOH solution was gradually added to the obtained mixed aqueous solution to precipitate a sparingly soluble salt (precursor). In the process of precipitating this precursor, the mixed aqueous solution was maintained at pH 11 and the temperature at 75°C. In addition, the mixed aqueous solution was also stirred to prevent uneven pH in the mixed aqueous solution. This stirring operation was performed by bubbling with oxygen gas. After performing aging treatment for 24 hours while continuing bubbling with oxygen gas, the resulting precursor precipitate was collected by suction filtration. The collected precipitate was kept at 85°C to evaporate some of the water and make it into a paste. The obtained paste was transferred to an evaporating dish, heated to 120°C, and kept in that state for 3 hours for drying treatment to obtain a dried precursor. The obtained dried precursor was placed in a mortar and crushed with a pestle to obtain a powder. In this way, a precursor powder was obtained.

[0069] 2) Firing process The obtained precursor powder was subjected to a heat treatment in which it was heated to 500°C in an air atmosphere and held for 3 hours. The precursor powder after the heat treatment was washed with distilled water at 75°C and then suction filtered. The filtered precursor powder was then held at 120°C for 3 hours and dried. Thus, a calcined powder was obtained. The obtained powder was subjected to XRD analysis. A parallel beam X-ray diffractometer was used for the XRD analysis. The analysis conditions here were an X-ray source of CuKα, a tube voltage of 15 kV, a tube current of 15 mA, a scan speed of 1 degree / min, and a step width of 0.01 degree. As a result of the analysis, it was confirmed that the main phase of the calcined powder was a pyrochlore type crystal of Bi2Ru2O7 from the obtained diffraction chart pattern.

[0070] In other words, it was confirmed that a pyrochlore-type bismuth ruthenium composite oxide (air electrode catalyst) was obtained by this firing process. The amount of the pyrochlore-type bismuth ruthenium composite oxide obtained was approximately 12 g.

[0071] Regarding the obtained powder of bismuth ruthenium composite oxide, secondary electron images were observed under a scanning electron microscope, and it was found that the particle size of the bismuth ruthenium composite oxide was 0.1 μm or less.

[0072] (2) Manufacturing of air electrodes Ni powder was prepared as an aggregate of Ni particles. The Ni particles were filament-shaped and had an average particle size of 10 to 20 μm.

[0073] Furthermore, a polytetrafluoroethylene (PTFE) dispersion and ion-exchanged water were prepared.

[0074] Nickel powder, polytetrafluoroethylene (PTFE) dispersion, and ion-exchanged water were added to the bismuth ruthenium composite oxide powder (air electrode catalyst) obtained as described above and mixed. At this time, the bismuth ruthenium composite oxide powder was 20 parts by weight, the nickel powder was 70 parts by weight, the PTFE dispersion was 10 parts by weight, and the ion-exchanged water was 10 parts by weight, and mixed uniformly to produce an air electrode mixture paste.

[0075] The obtained air electrode mixture paste was formed into a sheet, and this sheet-shaped air electrode mixture paste was dried at room temperature of 25°C, and then pressed onto a nickel mesh with a mesh number of 60, a wire diameter of 0.08 mm, and an opening ratio of 60%, thereby obtaining an intermediate air electrode product.

[0076] Next, the obtained intermediate product was heat-treated (sintered). The heat treatment conditions were that the intermediate product was heated to a heat treatment temperature of 340°C in a nitrogen gas atmosphere and held at this temperature for 13 minutes. The heat-treated intermediate product was cut into a length of 40 mm and a width of 40 mm, thereby obtaining an air electrode 16. The thickness of this air electrode 16 was 0.23 mm. In the obtained air electrode 16, the amount of bismuth ruthenium composite oxide powder (air electrode catalyst) was 0.25 g.

[0077] (3) Manufacturing of negative electrodes The metallic materials Nd, Mg, Ni, and Al were mixed to a predetermined molar ratio, then placed in a high-frequency induction melting furnace and melted under an argon gas atmosphere. The resulting molten metal was poured into a mold and cooled to room temperature of 25°C to produce an ingot.

[0078] Next, this ingot was subjected to a heat treatment in which it was held in an argon gas atmosphere at a temperature of 1000°C for 10 hours, and then cooled to room temperature of 25°C. After cooling, the ingot was mechanically pulverized in an argon gas atmosphere to obtain a rare earth-Mg-Ni based hydrogen storage alloy powder. The volume average particle size (MV) of the obtained rare earth-Mg-Ni based hydrogen storage alloy powder was measured by a laser diffraction / scattering type particle size distribution measuring device. As a result, the volume average particle size (MV) was 60 μm.

[0079] The composition of this hydrogen storage alloy powder was analyzed by inductively coupled plasma spectrometry (ICP), and found to be Nd 0.89 Mg 0.11 Ni 3.33 Al 0.17 It was.

[0080] Here, the electrochemical alloy capacity of the obtained hydrogen storage alloy was measured. Specifically, a measurement sample was prepared by setting aside a part of the hydrogen storage alloy powder obtained as described above, and nickel powder was prepared. Then, 0.25 g of the hydrogen storage alloy powder as the measurement sample was mixed with 0.75 g of nickel powder to prepare a mixed powder, and the mixed powder was molded to prepare a circular pellet electrode with a diameter of 10 mm.

[0081] Next, 100 mL of 8 mol / L KOH aqueous solution was poured into a cylindrical resin container, and a pellet electrode and a mercury oxide reference electrode were placed in the center of the container and in the KOH aqueous solution. Furthermore, a nickel hydroxide counter electrode with a sufficiently large capacity relative to the negative electrode (pellet electrode) was placed along the edge of the container. In this way, a battery with a negative electrode capacity regulation was formed. A charge / discharge test was performed on this battery, in which a charging operation was performed at 0.5 It for 200 minutes, and a discharging operation was performed at 0.5 It until the negative electrode potential was -0.3 V relative to the mercury oxide reference electrode, to determine the electrochemical alloy capacity. The negative electrode capacity calculated assuming the alloy capacity to be 300 mAh / g was set to 1 It.

[0082] To 100 parts by weight of the obtained hydrogen storage alloy powder, 0.2 parts by weight of sodium polyacrylate powder, 0.04 parts by weight of carboxymethyl cellulose powder, 1.0 part by weight of a styrene butadiene rubber dispersion, 0.3 parts by weight of carbon black powder, and 22.4 parts by weight of water were added and kneaded in an environment of 25°C to prepare a negative electrode mixture paste.

[0083] This negative electrode mixture paste is applied to a substrate with a surface density (weight) of approximately 300 g / m 2 The mixture was then filled into a foamed nickel sheet having a thickness of about 1.7 mm. The negative electrode mixture paste was then dried to obtain a foamed nickel sheet filled with the negative electrode mixture. The obtained sheet was rolled to increase the amount of alloy per unit volume, and then cut into a length of 40 mm and a width of 40 mm. In this manner, the negative electrode 12 was obtained. The thickness of the negative electrode 12 was 0.75 mm, and the negative electrode capacity calculated from the above electrochemical alloy capacity was 2500 mAh.

[0084] (4) Manufacturing of air hydrogen secondary batteries The obtained air electrode 16 and negative electrode 12 were stacked with a separator 14 sandwiched between them to produce an electrode group 10. The separator 14 used in the production of this electrode group 10 was formed of a nonwoven fabric made of polypropylene fibers having sulfonic groups, and had a thickness of 0.2 mm (basis weight 100 g / m 2 ) was.

[0085] Next, the container body 6 was prepared, and the above-mentioned electrode group 10 was housed in this container body 6. At this time, a foamed nickel sheet serving as the adjustment member 36 was placed on the bottom wall 18 of the container body 6, and the electrode group 10 was placed on this adjustment member 36. Here, the foamed nickel sheet serving as the adjustment member 36 had a thickness of 1 mm and was in the shape of a square measuring 40 mm in length and 40 mm in width.

[0086] Next, the water-repellent and ventilation member 40 was disposed on the electrode group 10 (on the air electrode 16). Here, the water-repellent and ventilation member 40 was formed by combining a PTFE porous membrane 42 having a length of 45 mm, a width of 45 mm, and a thickness of 0.1 mm, and a nonwoven fabric diffusion paper 44 having a length of 40 mm, a width of 40 mm, and a thickness of 0.2 mm.

[0087] Next, the lid 8 was placed on the container body 6 to close the opening 22. At this time, the water-repellent ventilation member 40 was brought into close contact with the inner surface 28 of the lid 8 so that the area including the ventilation passage 30, the inlet ventilation hole 32, and the outlet ventilation hole 34 was entirely covered with the water-repellent ventilation member 40. Here, the ventilation passage 30 has a single serpentine shape as a whole. The cross section of the ventilation passage 30 is rectangular, with the vertical dimension of the rectangle being 1 mm and the horizontal dimension of the rectangle being 1 mm. The ventilation passage 30 is open on the water-repellent ventilation member 40 side.

[0088] The container 4 formed by combining the container body 6 and the lid 8 has peripheral edges 46, 48 sandwiched from above and below by connectors 50, 52. A resin packing (not shown) is provided at the contact area between the container body 6 and the lid 8 to prevent leakage of the alkaline electrolyte.

[0089] Next, a 5 mol / L KOH aqueous solution was injected as the alkaline electrolyte 82 into the electrolyte reservoir 80. The amount of the KOH aqueous solution injected at this time was 50 mL. In this manner, a battery 2 as shown in FIG. 1 was produced.

[0090] An air electrode lead 54 is electrically connected to the air electrode 16, and an anode lead 56 is electrically connected to the anode 12, and these air electrode lead 54 and anode lead 56 appropriately extend from the lead wire outlets 24, 26 to the outside of the container 4 while maintaining the airtightness and liquid-tightness of the container 4. An air electrode terminal 58 is attached to the tip of the air electrode lead 54, and an anode terminal 60 is attached to the tip of the anode lead 56.

[0091] Example 2 An air-hydrogen secondary battery was manufactured in the same manner as in Example 1, except that Bi(NO3)3·5H2O and RuCl3·3H2O were weighed out so that the molar concentration ratio of Ru was 1.00 and Bi was 0.80. Here, it was confirmed that the main phase of the bismuth ruthenium composite oxide (air electrode catalyst) of Example 2 was a pyrochlore-type crystal of Bi2Ru2O7.

[0092] Example 3 Except for further carrying out an acid treatment process on the bismuth ruthenium composite oxide obtained through the firing process and removing by-products, an air-hydrogen secondary battery was manufactured in the same manner as in Example 1. Here, the procedure of the acid treatment process will be described below.

[0093] First, 1 g of bismuth ruthenium composite oxide powder was placed in a stirring tank with a stirrer together with 20 mL of an aqueous nitric acid solution, and acid treatment was performed by stirring for 1 hour while maintaining the temperature of the aqueous nitric acid solution at 25° C. Here, the concentration of the aqueous nitric acid solution was 2 mol / L.

[0094] After the stirring was completed, the powder of the bismuth ruthenium composite oxide was taken out from the nitric acid aqueous solution by suction filtration. The taken out powder of the bismuth ruthenium composite oxide was washed with 1 liter of distilled water heated to 75°C. After washing, the powder of the bismuth ruthenium composite oxide was dried by keeping it in an atmosphere of 120°C for 3 hours.

[0095] In this manner, an acid-treated bismuth ruthenium composite oxide powder, i.e., an air electrode catalyst powder for an air secondary battery, was obtained. By carrying out the acid treatment as described above, amorphous by-products generated in the manufacturing process of the bismuth ruthenium composite oxide were removed from the obtained air electrode catalyst.

[0096] It was also confirmed that the main phase of the bismuth ruthenium composite oxide (air electrode catalyst) of Example 3 was a pyrochlore type crystal of Bi2Ru2O7.

[0097] Example 4 The bismuth ruthenium composite oxide obtained through the firing step was further subjected to the acid treatment step shown in Example 3, and an air-hydrogen secondary battery was produced in the same manner as in Example 2, except that by-products were removed. It was also confirmed that the main phase of the bismuth ruthenium composite oxide (air electrode catalyst) of Example 4 was a pyrochlore type crystal of Bi2Ru2O7.

[0098] Comparative Example 1 An air-hydrogen secondary battery was produced in the same manner as in Example 1, except that Bi(NO3)3·5H2O and RuCl3·3H2O were weighed out so that the molar concentration ratio of Ru was 1.00:Bi was 1.00.

[0099] It was confirmed that the main phase of the bismuth ruthenium composite oxide (air electrode catalyst) of Comparative Example 1 was a pyrochlore type crystal of Bi2Ru2O7.

[0100] Comparative Example 2 An air-hydrogen secondary battery was manufactured in the same manner as in Example 1, except that Bi(NO3)3·5H2O and RuCl3·3H2O were weighed out so that the molar concentration ratio of Ru to Bi was 1.00:1.00, and that the bismuth ruthenium composite oxide obtained through the firing process was subjected to an acid treatment step similar to the acid treatment step shown in Example 3 using a nitric acid aqueous solution with a concentration of 5 mol / L to remove by-products.

[0101] It was confirmed that the main phase of the bismuth ruthenium composite oxide (air electrode catalyst) of Comparative Example 2 was a pyrochlore type crystal of Bi2Ru2O7.

[0102] 2. Evaluation of air electrode catalyst and air hydrogen secondary battery

[0103] (1) EXAFS measurements As samples for EXAFS measurement, portions of the bismuth ruthenium composite oxides of Examples 1 to 4 and Comparative Examples 1 and 2 were previously collected.

[0104] Then, the samples for the EXAFS measurement were subjected to EXAFS measurement using synchrotron X-rays from a large synchrotron radiation facility (for example, Super Photon ring-8: SPring8). The detailed procedure is as follows.

[0105] First, the sample was pressed into a pellet shape, and the pellet-shaped sample was placed on the sample stage of the measuring instrument. Then, the sample was irradiated with X-rays in a room temperature (25°C) environment, and the X-ray absorption was directly measured by the transmission method. Specifically, the ROI (region of interest) was set to 13.427 keV, which is the Bi-L3 absorption edge energy, and the absorbance was measured by measuring the X-ray intensity before and after the sample transmission while scanning the energy of the incident X-ray by changing the angle of the Si (111) analyzing crystal. The obtained data was analyzed using Athena, an analysis software for processing XAFS data.

[0106] Here, the analysis results obtained for the sample of Example 1 and the sample of Comparative Example 1 are shown in Figs. 3 to 10. Fig. 3 is a graph showing the absorption spectrum of raw data for the sample of Example 1. Fig. 4 is a graph in which the background absorption region shown by the dashed line in Fig. 3 is removed by fitting and the absorbance is normalized. Fig. 5 is a graph showing the spectrum of EXAFS oscillations extracted by fitting with a spline curve. k on the horizontal axis is the wave number corresponding to the energy of the emitted photoelectrons, and in this analysis, the analysis was performed with k-weight set to 3. Fig. 6 is a graph showing the Fourier transform (FT) of the obtained EXAFS oscillations, which is a spectrum showing a peak according to the interatomic distance (radial structure function reflecting the atomic distribution in one-dimensional direction). Fig. 7 is a graph showing the absorption spectrum of raw data for the sample of Comparative Example 1. Fig. 8 is a graph in which the background absorption region shown by the dashed line in Fig. 7 is removed by fitting and the absorbance is normalized. Fig. 9 is a graph showing the spectrum of EXAFS oscillations extracted by fitting with a spline curve. The k on the horizontal axis is the wave number corresponding to the energy of the emitted photoelectron, and in this analysis, the k-weight was set to 3. Figure 10 is a graph showing the Fourier transform (FT) of the obtained EXAFS vibration, and is a spectrum showing peaks corresponding to the interatomic distance (radial structure function reflecting the atomic distribution in one dimensional direction).

[0107] (2) Battery characteristic evaluation The air hydrogen secondary batteries of Examples 1 to 4 and Comparative Examples 1 and 2 were repeatedly charged and discharged in an atmosphere of 25° C. via the air electrode terminal 58 and the negative electrode terminal 60 at 0.1 It for 10 hours, and then discharged at 0.2 It until the battery voltage reached 0.4 V. This was defined as 1.0 It, which is 2.0 Ah, which corresponds to 80% of the negative electrode capacity.

[0108] In the above-mentioned charge and discharge operation, a rest period of 10 minutes was provided between charge and discharge, and between discharge and charge. The open circuit voltage (OCV) of the air hydrogen secondary battery was measured during this rest period. Here, the OCV during the rest period between charge and discharge was defined as the OCV during charge, and the OCV during the rest period between discharge and charge was defined as the OCV during discharge. In this battery, when a voltage exceeding 1.3 V could not be generated even when charged, it was determined that a short circuit had occurred inside the battery. Therefore, the number of cycles until the OCV during charge became 1.3 V or less was counted, and the number of cycles was defined as the cycle life. The number of cycles obtained is shown in Table 1. In addition, for the bismuth ruthenium composite oxides contained in the air hydrogen secondary batteries of Examples 1 to 4 and Comparative Examples 1 and 2, k obtained from EXAFS measurement of the Bi-L3 absorption edge was 3 3.2 Å in the vibrational spectrum of χ(k) -1 <k<4.9Å -1 The intensity of the peak in the range of 4.9 Å is defined as A. -1 <k<5.7Å -1 Assuming that the intensity of a peak existing in this range is B, the peak intensity A, the peak intensity B, and the peak intensity ratio B / A between the peak intensity A and the peak intensity B are also shown in Table 1. Furthermore, the relationship between the peak intensity ratio B / A of the EXAFS oscillation and the number of cycles for the air-hydrogen secondary batteries of Examples 1 to 4 and Comparative Examples 1 and 2 is shown in FIG.

[0109] During the above-mentioned charging and discharging operations, regardless of charging and discharging, air was constantly supplied to the ventilation path 30 at a rate of 33 mL / min by introducing air through the inlet ventilation hole 32 and discharging air through the outlet ventilation hole 34. The air supplied to the ventilation path 30 was air (CO2 concentration: about 100 ppm) that had been bubbled through a KOH aqueous solution.

[0110] [Table 1]

[0111] (3) Discussion k obtained from EXAFS measurement of Bi-L3 absorption edge 33.2 Å in the vibrational spectrum of χ(k) -1 <k<4.9Å -1 Intensity A of the peaks in the range of 4.9 Å -1 <k<5.7Å -1 From Table 1 and FIG. 11 which summarize the relationship between the intensity ratio B / A of the peak intensity B present in the range and the number of cycles of the air-hydrogen secondary battery, the following can be seen.

[0112] In Examples 1 to 4, the number of cycles is 43 to 89, whereas in Comparative Example 1, the number of cycles is 2, and in Comparative Example 2, the number of cycles is 15. The more the number of cycles, the longer the cycle life is, which means that the occurrence of internal short circuits is suppressed. Therefore, it can be said that the occurrence of internal short circuits is suppressed in Examples 1 to 4 compared to Comparative Examples 1 and 2. Here, when comparing the values ​​of B / A between Examples 1 to 4 and Comparative Examples 1 and 2, the values ​​of B / A are higher in Examples 1 to 4 than in Comparative Examples 1 and 2. In other words, the higher the value of B / A, the more the occurrence of internal short circuits is suppressed. This is considered to be because the higher the value of B / A, the higher the dissolution resistance of the main phase of the pyrochlore structure of Bi2Ru2O7 becomes, and the dissolution of Bi is suppressed.

[0113] In addition, Comparative Example 2 is an embodiment in which the by-products are removed by subjecting Comparative Example 1 to an acid treatment. Comparative Example 2 has a higher number of cycles than Comparative Example 1, and the occurrence of internal short circuits is suppressed. This is believed to be because the by-products are removed and the elution of Bi caused by the by-products is suppressed. In other words, it can be said that removing the by-products is effective in extending the cycle life. However, Comparative Example 2 has a much lower number of cycles than Examples 1 and 2, which do not have an acid treatment. From this, it is believed that the higher the value of the peak intensity ratio B / A, the less likely highly soluble by-products are to be generated. From the above, it is believed that the higher the value of the peak intensity ratio B / A, the less highly soluble by-products are generated, and the higher the resistance to dissolution of the main phase of the pyrochlore structure of Bi2Ru2O7.

[0114] The present invention is not limited to the above-mentioned embodiments and examples. For example, the present invention is not limited to air-hydrogen secondary batteries, and may be applied to other air secondary batteries using Zn, Al, Mg, Li, etc. as the metal used in the negative electrode.

[0115] <Aspects of the present invention> The first aspect of the present invention is a bismuth ruthenium composite oxide having a pyrochlore-type crystal structure represented by the composition formula Bi2Ru2O7, and k obtained from extended X-ray absorption fine structure (EXAFS) measurement of Bi-L3. 3 3.2 Å in the vibrational spectrum of χ(k) -1 <k<4.9Å -1 The intensity of the peak in the range of 4.9 Å is defined as A. -1 <k<5.7Å -1 When the intensity of the peak existing in the range is B, the intensity ratio B / A of A and B is 0.28

[0116] According to the first aspect, the dissolution resistance of the bismuth ruthenium composite oxide but This increases the temperature and suppresses the dissolution of bismuth. R As a result, the growth of bismuth dendrites is suppressed, making it possible to suppress the occurrence of internal short circuits.

[0117] A second aspect of the present invention relates to an air electrode catalyst for an air secondary battery, wherein in the first aspect of the present invention described above, the bismuth ruthenium composite oxide contains at least one element selected from Na, Ca, Pb, rare earth elements, Ir, Mn, Ti, V, Nb and Mo.

[0118] According to the second aspect, the dissolution resistance of the bismuth ruthenium composite oxide is increased, which contributes to improving the cycle characteristics of the battery.

[0119] ​A third aspect of the present invention relates to an air electrode catalyst for an air secondary battery, wherein the molar ratio Bi / Ru of Bi and Ru contained in the bismuth ruthenium composite oxide is 0.75≦Bi / Ru≦0.80 in the first or second aspect of the present invention described above.

[0120] According to the third aspect, the dissolution resistance of the bismuth ruthenium composite oxide is further improved.

[0121] A fourth aspect of the present invention relates to a method for producing an air electrode catalyst for an air secondary battery according to any one of the first to third aspects of the present invention described above, comprising a coprecipitation step of adding an alkaline aqueous solution to an acidic aqueous solution containing a metal salt of Bi and a metal salt of Ru to form a precursor containing oxides of Bi and Ru, and a calcination step of heat-treating the precursor in an air atmosphere at a temperature in the range of 300°C or more and 700°C or less.

[0122] According to the fourth aspect, a bismuth ruthenium composite oxide having excellent resistance to dissolution can be obtained.

[0123] A fifth aspect of the present invention relates to an air secondary battery comprising: an electrode group including an air electrode and a negative electrode stacked with a separator interposed therebetween; and a container accommodating the electrode group together with an alkaline electrolyte, wherein the air electrode contains the air electrode catalyst for air secondary batteries according to any one of the first to third aspects of the present invention described above.

[0124] According to the fifth aspect, an air secondary battery having improved cycle life characteristics compared to conventional air secondary batteries can be obtained.

[0125] A sixth aspect of the present invention relates to the air secondary battery according to the fifth aspect of the present invention, wherein the negative electrode contains a hydrogen storage alloy.

[0126] According to the sixth aspect, an air hydrogen secondary battery having excellent cycle life characteristics can be obtained. [Explanation of symbols]

[0127] 2. Battery (air hydrogen secondary battery) 4 containers 6 Container body 8 Lid 10 electrode groups 12 Negative electrode 14 Separator 16 Air electrode (positive electrode) 30 Ventilation Channel 40 Water-repellent and breathable materials

Claims

1. A bismuth ruthenium composite oxide having a pyrochlore-type crystal structure represented by the composition formula Q2-xR2-yO7-z (wherein Q represents Bi or an element in which the Bi is partially substituted with at least one selected from Na, Ca, Pb and rare earth elements, R represents Ru or an element in which the Ru is partially substituted with at least one selected from Ir, Mn, Ti, V, Nb and Mo, and x, y and z each represent a value between 0 and 1, and a molar ratio Q / R of Q and R satisfies 0.75≦Q / R≦0.80), 3 The k obtained from the extended X-ray absorption fine structure (EXAFS) measurement 3 3.2 Å in the vibration spectrum of χ(k) -1 <k<4.9 Å -1 The intensity of the peak present in the range of 4.9 Å is designated as A. -1 <k<5.7 Å -1 The air electrode catalyst for an air secondary battery is made of a bismuth ruthenium composite oxide, in which, when the intensity of a peak existing in the range of A is B, the intensity ratio B / A of A and B is 0.28<B / A<0.

44.

2. The air electrode catalyst for an air secondary battery as described in claim 1, wherein Q is selected as Bi and R is selected as Ru.

3. A method for producing an air electrode catalyst for an air secondary battery according to any one of claims 1 to 2, comprising the steps of: a coprecipitation step of adding an alkaline aqueous solution to an acidic aqueous solution containing a metal salt of Bi and a metal salt of Ru to form a precursor containing oxides of Bi and Ru; a calcination step of heat-treating the precursor in an air atmosphere at a temperature range of 300° C. or more and 700° C. or less; The present invention relates to a method for producing an air electrode catalyst for an air secondary battery.

4. an electrode group including an air electrode and a negative electrode stacked with a separator interposed therebetween; a container that contains the electrode group together with an alkaline electrolyte, An air secondary battery, wherein the air electrode comprises the air electrode catalyst for an air secondary battery according to claim 1 or 2.

5. The air secondary battery according to claim 4 , wherein the negative electrode contains a hydrogen storage alloy.

Citation Information

Patent Citations

  • Positive electrode, air secondary battery using the same, and method for manufacturing positive electrode

    JP2016152068A

  • Manufacturing method of catalyst for air secondary battery, manufacturing method of air secondary battery, catalyst for air secondary battery, and air secondary battery

    JP2019179592A

  • Catalyst of oxygen generation reaction and oxygen reduction reaction

    JP2019195775A